Rural Economic Development (Management Evaluation of Village Owned Enterprises (Bumdes) "Berkat" in Tulap Village, Kombi District, Minahasa Regency) - Lidya, Gerungan Maya; Mandagi, Marthinus; Tumbel, Goinpeace H. (Technium Social Sciences Journal, 2024)
This research aims to evaluate, analyze, and describe how the Village-Owned Enterprises (BUMDes) "Berkat" are managed in Tulap Village, Kombi District. In this research, the author used a qualitative research approach with the research object namely the Village-Owned Enterprise (BUMDes) "Berkat" Tulap Village, Kombi District. The focus of this research is the evaluation of the "Berkat" Village-Owned Enterprise in Supporting the economic development of Tulap Village, Kombi District with a sub-focus: evaluation of planning, implementation, and supervision. The results of the research show that 1) The planning stage for managing business activities at BUMDes "Berkat" in Tulap Village has not been implemented properly, thus affecting the process of implementing business activities so that it has not been able to have a significant impact on economic development in Tulap Village; 2) The implementation of each business activity at the BUMDes "Berkat" Tulap Village has not been optimal so that the stated goal of establishing the BUMDes "Berkat" Tulap Village cannot be achieved due to the lack of ability and knowledge of the BUMDes management in carrying out each business activity; 3) It is certain that supervision of BUMDes "Berkat" in Tulap Village is not going well. This is due to a lack of knowledge from the supervisors appointed by the government and also a lack of attention from the relevant agencies regarding the management of BUMDes so the process of achieving goals cannot run well.